Attitude and knowledge on oil palm farm biodiversity and willingness to participate in sustainable palm oil certification among oil palm smallholders in Tanjung Karang, Selangor - Firdaus, Muhammad Abrisam (2016)
Oil palm or scientifically known as Elaeis guineensis Jacq. is the most important commodity crop as compared to other crops in Malaysia. Oil palm smallholders play very important role in the Malaysia. There has been lack of studies on oil palm smallholder’s knowledge and attitude toward oil palm farmland biodiversity and their willingness to participate in the sustainable palm oil certification scheme. There the objectives of study the biodiversity were to assess knowledge and attitude of oil palm smallholders toward biodiversity in oil palm smallholders, and examine their willingness to participate in sustainable palm oil certification scheme. This study was based on structured interviews with 50 oil palm in Tanjung Karang, Selangor. This study found that knowledge of oil palm smallholders on farm biodiversity was low and viewed biodiversity from a narrow perspective by focusing on pest animals while neglecting other species directly related to farmland biodiversity. In terms at attitude toward biodiversity, most of smallholders felt angry with wild animals and tend to chase the animal away from the farm. The study also found that all respondents willing to join sustainable palm oil certification but willing to pay a very slow annual certification fees.